UPAYA DIPLOMATIK MALAYSIA TERHADAP MYANMAR DALAM MENANGANI PEMBANTAIAN ETNIS MUSLIM ROHINGYA (2015-2017) - Ranti Yunita; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research describes the efforts of diplomatic pressure in Malaysia against Myanmar in dealing with the slaughter of Rohingya ethnic Muslims then, explain Malaysia and Myanmar diplomatic relations before the heated conflict of Rohingya Muslim ethnic massacre in Rakhine. The purpose of this study was to analyze and find out the shape and efforts of Malaysia to help the Muslim ethnic Rohingya. The humanitarian crisis that occurred in Myanmar received various criticisms from several countries such as Malaysia, Indonesia and other countries. This is due to the large number of Rohingya refugees who have fled to neighboring countries to get protection. the large number of Rohingya refugees can disrupt security stability in the Southeast Asia region, and cause concern for the country targeted by Rohingya refugees. Malaysia, one of ASEAN members, protested against the actions of the Myanmar government which had violated human rights towards its ethnic groups. Malaysia considers Myanmar's actions out of bounds and must be stopped so that there are no more victims. As for Malaysia's efforts to help Rohingya ethnic groups such as doing diplomacy and inviting ASEAN member countries and to work together to help their spirits. The existence of non-intervention principles that are used asean makes this problem unresolved. Keywords: Diplomacy, Ethmic Cleansing, Principle of non-intervention